Dreaming the Hammer Back: On Teodoras Bieliackinas’s Translation of Þrymskviða - Steponavičiūtė - Aleksiejūnienė, Ieva (Scandinavistica Vilnensis, 2019)
The paper deals with the legacy of Teodoras Bieliackinas (1907–1947), a Lithuanian exile in Iceland, the first Lithuanian professional Scandinavianist and the first translator of Eddic poetry into Lithuanian. With its background of the “biographical turn” in translation studies and with the help of the concept of “differential margin” proposed by Theo Hermans, the paper focuses on Bieliackinas’s rendition of Þrymskviða into Lithuanian. The aim is to trace the translator’s own ideological agenda, which appears to have been inscribed by him into the Old Norse song. It is claimed that the song about the loss and recovery of Thor’s hammer has been invested by Bieliackinas with a new – allegorical – meaning and can be read as a message of hope that Bieliackinas was sending to his countrymen who, like himself, were scattered around the world and mourned the loss of their state.
Keywords: Teodoras Bieliackinas; differential margin; Lithuanian; translation; Old Norse; Þrymskviða; Scandinavian studies